2021
DOI: 10.1149/2162-8777/abe97b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV Radiation on Oxidation for Ru CMP

Abstract: As feature size continue to decrease, traditional copper (Cu) interconnections will encounter many problems. Ruthenium (Ru) is selected as a barrier material and even a future interconnection metal material because of its many advantages. However, due to its high hardness and chemical inertness, Ru is difficult to be removed during chemical mechanical polishing (CMP). In this study, the effect of UV-activated potassium persulfate (K2S2O8) on the removal rate of Ru CMP was studied. X-ray photoelectron spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…[ 189 ] Therefore, oxidizing agents, such as potassium perchlorate (KClO 4 ), potassium permanganate (KMnO 4 ), sodium hypochlorite (NaClO), potassium bromate (KBrO 3 ), potassium persulfate (K 2 S 2 O 8 ), potassium periodate (KIO 4 ), and hydrogen peroxide (H 2 O 2 ), have been screened. [ 190 , 191 , 192 , 193 , 194 , 195 , 196 ] The presence of IO 4 − ions in the slurry promotes the formation of mechanical structures and porous oxide layers on the Ru surface. It accelerates surface corrosion, thereby increasing the Ru removal rate.…”
Section: Next‐generation Interconnect Materialsmentioning
confidence: 99%
“…[ 189 ] Therefore, oxidizing agents, such as potassium perchlorate (KClO 4 ), potassium permanganate (KMnO 4 ), sodium hypochlorite (NaClO), potassium bromate (KBrO 3 ), potassium persulfate (K 2 S 2 O 8 ), potassium periodate (KIO 4 ), and hydrogen peroxide (H 2 O 2 ), have been screened. [ 190 , 191 , 192 , 193 , 194 , 195 , 196 ] The presence of IO 4 − ions in the slurry promotes the formation of mechanical structures and porous oxide layers on the Ru surface. It accelerates surface corrosion, thereby increasing the Ru removal rate.…”
Section: Next‐generation Interconnect Materialsmentioning
confidence: 99%
“…To meet the requirements of efficient ruthenium removal, the researchers screened a number of oxidizers, such as KMnO 4 (potassium permanganate), KClO 4 (potassium perchlorate), NaIO 4 (sodium periodate), K 3 [Fe(CN) 6 ] (potassium ferricyanide), potassium peroxymonosulfate (oxone), K 2 S 2 O 8 (potassium persulfate), KIO 4 (potassium periodate), (NH 4 ) 2 S 2 O 8 (ammonium persulphate) and H 2 O 2 (hydrogen peroxide), among which KIO 4 and H 2 O 2 receive widespread attention. [7][8][9]12,[14][15][16][17][18][19][20][21] H. Cui et al 22 studied the effect of various oxidizers on the removal rate of ruthenium from the perspective of surface corrosion and oxidation. The experimental results suggested that the existence of IO 4…”
Section: Introductionmentioning
confidence: 99%
“…To meet the increasing demand for barrier layer materials, the use of Ru has become the preferred material for low-technology nodes. [7][8][9][10][11] The schematic illustration of Ru-based Cu CMP is presented in Fig. 1.…”
mentioning
confidence: 99%